"Rational Calculations by Rational Men": Public Perception of the Transition from Private to Public Atomic Fallout Shelters during the Cold War, 1961-1969 - Johnson, Benjamin (My University, 2018)
This thesis argued that public perception of private fallout shelters in the United States during the 1950s and early 1960s and public fallout shelters by the mid-1960s was split between different camps. Debates in newspapers revolved around three key issues: the effectiveness of the shelters given the destructiveness of nuclear fallout and thermonuclear weapons; appropriate standards regarding the marking and stocking public fallout shelters, and the concern that authorities lacked the will or adequate means to prepare the public for nuclear war. These debates extended to the federal government as well as the American public and are reflected in government studies and federal civil defense manuals as early as the Truman and Eisenhower presidencies. The benefits of private versus public shelters were closely weighed with civil defense funding and the desire to placate the fears of the public in mind. The Kennedy Administration's decision to adopt public shelters was a response to these debates and a recognition that, irrespective of funding issues, government sponsorship of shelters had become a political necessity as a form of panic control.
Keywords: Cold war--Social aspects--United States; Fallout shelters--Social aspects--United States